An Inconvenient Truth: The Added Value of Transvaginal Imaging of the Internal Iliac and Adnexal Veins for Pelvic Congestion Syndrome. Issue 3 (September 2019) - Walsh, Michelle; Ahern, Mary; Zahiri, Nazha; David, Angela; Lyons, Shannon; Romero, Javier; Hedgire, Sandeep; Ghoshhajra, Brian
Pelvic congestion syndrome is a chronic condition involving varicose veins in the pelvic area, resulting in dull aching pain, pelvic heaviness, palpable varicosities, and dyspareunia. The primary diagnostic modalities, computed tomography (CT) angiography and magnetic resonance (MR) angiography, can be time-consuming, expensive, and carry the risks of diagnostic radiation (CT) and intravenous contrast (CT and MR), and may not offer dynamic vascular information (CT). Recently, an increased role for ultrasound has been proposed in the diagnosis of pelvic congestion; however, the role of transvaginal (TV) duplex ultrasound has not been thoroughly investigated. Our study aims to evaluate the utility of a TV approach in the evaluation of valvular incompetence time (VIT) in seconds of the internal iliac and adnexal veins. A waiver of consent was granted by our Institutional Review Board for this retrospective review. A cohort of 36 women undergoing ultrasound evaluation for pelvic congestion syndrome was analyzed. Transvaginal and transabdominal (TA) images were obtained with reverse Trendelenburg positioning for imaging of the internal iliac veins with Valsalva maneuver to evaluate VIT, at the same visit, and the yield of each approach was compared for the presence of VIT. The number of vessels visualized, VIT, diagnostic success, and number of abnormal vessels were recorded. Between September 2018 and February 2019, 36 women underwent both TA and TV imaging. A total of 72 (100%) internal iliac veins were visualized by TV, but only 15 (21%) by TA. Of the 72 internal iliac veins imaged, 12 (17%) were shown to have valvular incompetence by TV exam, whereas only 2 (3%) were identified by TA, both of which were identified TV. Transabdominal images, when limited, were usually due to bowel gas. Transvaginal images had a higher yield for detection of internal iliac vein VIT, suggesting that the TV approach may be more sensitive and potentially more accurate versus a TA-only protocol.